Protecting The Interests Of The Child Through Freedoms, Human Rights, And The Rule Of Law - Skenderaj, Mallengjim (European Scientific Journal, ESJ, 2016)
Parents, authorities, and courts in their decisions and activities must have as a primary consideration of the best interests of the child. This is exactly what article 2 of the Family Code says. Also, lawmakers also described this in articles 116-122 of the Constitution. This refers to any ratified international agreement which constitutes part of the internal system as published in the Official Gazette of the Republic of Albania. Therefore, it gives people a priority over the laws of the country that they do not agree with. This study aims in understanding the relations between parents and children through parental responsibility and principles which underlie the exercise of parental responsibility. In protecting the interest of the child, there has been an evolution in anthropological and historical aspect of the legal opinion. However, there is a clear difference between the concept of "patria potestas" of the Roman law and parental power conceived by the modern right. The first represents an institute which primarily protects the interests of "Pater familias". Consequently, the head of each family exercise their duties, roles, and authority, majorly in view of the family’s welfare. In the second which is the modern concept, the cornerstone of parental power lies not with the idea, but this power is conceived based on the best interests of the child. It states that parents, competent authorities, and courts in the decisions making process, must have the best interests of the child as the primary consideration.